2018
DOI: 10.4314/as.v16i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of land use on infiltration characteristics of soils in Northern Akwa Ibom State, South-eastern Nigeria

Abstract: Knowledge of infiltration characteristics of soils is necessary for designing quality soil management and conservation practices on agricultural and urban lands. This is predicated upon accurate evaluation of the infiltration characteristics of the soil. A study was conducted to evaluate the effect of three land use practices, namely, oil palm plantation (OP), bush fallow (FL) and continuous cultivation (CC) on the infiltration characteristics of soils formed on sandstone parent material in northern Akwa Ibom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
(25 reference statements)
2
9
0
2
Order By: Relevance
“…Eze et al (2011), observed that the infiltration rate of a sandy soil under forest was higher than under sparse vegetation and bare cultivation. Ogban (2017), reported significantly (p≤0.05) high infiltration rates in soil under oil palm compared to fallow and cultivated soil, and in the trend: OP>FL>CC. Differences between FL and CC were not significant.…”
Section: Introductionmentioning
confidence: 92%
“…Eze et al (2011), observed that the infiltration rate of a sandy soil under forest was higher than under sparse vegetation and bare cultivation. Ogban (2017), reported significantly (p≤0.05) high infiltration rates in soil under oil palm compared to fallow and cultivated soil, and in the trend: OP>FL>CC. Differences between FL and CC were not significant.…”
Section: Introductionmentioning
confidence: 92%
“…This implies increased rainwater infiltration/retention in the soil, such that palm trees serve as a biological measure of agricultural water conservation (Obalum et al, 2011). Regarding the required improvements in soil structural-hydraulic properties, oil palm plantation has severally been reported to be superior to arable cropping in southeastern Nigeria (Igwe, 2001;Ogban, 2017;Uzoma and Onwuka, 2018).…”
Section: Multipurose Roles Of Oil Palm Ecological Benefits Of the Oilmentioning
confidence: 99%
“…Water infiltration is also believed to increase with reduction in bulk density, establishment of cover crops, mulching, and incorporation of crop residues (Shukla et al, 2003a). Knowledge of soil infiltration characteristics is a required input in increasing irrigation water use efficiency, design of irrigation systems, and decrease water and soil losses, all of which are crucial factors in agriculture (Ogban and Utin, 2014). Infiltration data is also an important parameter in field drainage applications (Haghighi et al, 2011).…”
Section: Treatmentmentioning
confidence: 99%
“…Variation of the S parameter among treatments may be caused by the differences in continuity and arrangements of soil pores. The A parameter (Soil water transmissivity) is a gravity factor, which is due to the impact of pores on the flow of water through soil under the influence of gravity (Ogban and Utin, 2014). It governs the final steady state infiltration rate.…”
Section: Philip's Equationmentioning
confidence: 99%